Lipophilic bioactive compounds nano-micro encapsulation via coaxial electrohydrodynamic atomization: A review - Elnaz Z. Fallahasghari; Ioannis S. Chronakis; Ana C. Mendes (Food Hydrocolloids for Health)
Natural lipophilic bioactive compounds, which are essential for various physiological functions, present challenges in processing and formulation due to their physicochemical properties. Encapsulation techniques are utilized to improve their stability, solubility, and bioavailability. Electrohydrodynamic (EDH) processes, such as electrospinning and electrospraying, provide scalable methods for crafting nano-microfibers and capsules, making them ideal for encapsulating bioactive lipophilic compounds. Coaxial electrohydrodynamic processes generate core-shell structures with enhanced encapsulation performance, utilizing a broad range of polymers. This review discusses the research conducted over the past seven years on the core-shell electrosprayed capsules and electrospun fibers, for encapsulating natural lipophilic bioactive compounds. The aim is to promote the adoption of coaxial electrohydrodynamics as a straightforward and more sustainable encapsulation technology for lipophilic compounds.